The future of archives and recordkeeping : a reader - Hill, Jennie (London : Facet Pub., 2011)
The book offers a clearly organized approach to developments in archives and recordkeeping. The chapters are contributed by leaders in the field, and are grouped around the following four core themes: defining archives; shaping a discipline; archives 2.0: archives in society; archives in the information age: is there still a role for the archivist?
Includes bibliographical references and index.
rua 29/11/13
Loans
Keywords: Archives; Archives -- Technological innovations